Service provision for older forensic mental health patients: a scoping review of the literature - Walker, Kate (The journal of forensic psychiatry & psychology, 2021)
Older forensic psychiatric patients (defined as aged 50 or over) have complex needs and require specialized treatment to enable recovery and reduce risk. Little is known about what service provision is available for this population, so a scoping literature review was undertaken to establish the extent of service provision and if services are specifically modified or designed for this population. The literature was searched through academic journal databases and Google Scholar, and outputs were screened for suitability and assessed for quality. Eight studies (four qualitative, four quantitative) were included in the review. Studies were mixed in terms of methodological quality, and with several limitations. Qualitative data provided perceptions regarding positive (e.g., sufficient types of therapy) and negative (e.g., lack of age-appropriate services) aspects of interventions. Quantitative data were descriptive, focusing mainly on identifying provision available (e.g., art therapy, violence reduction) and where needs were not being met (e.g., physical needs, education). Results indicate little provision in place adapted specifically for older forensic psychiatric patients. Findings highlight the need for further research to understand and effectively implement interventions and service provision for older forensic mental health patients to ensure practice is evidence based.